Sociomathematical norms in online learning in the COVID-19 pandemic period - Samsul Maarif; Novia Oktarina; Sandi Sessu; Fitria Sulistyowati; Wikan Budi Utami (International Journal of Evaluation and Research in Education (IJERE), 2022)
This case study analyzed students' sociomathematical norms for the formation of study groups conducted by teachers, the role of sociomathematical norms on students' social interactions when learning mathematics, gender differences that can affect students' sociomathematical norms, and sociomathematical norms on derived material in terms of gender aspects among students. The nine subjects of this study were selected purposively. Data collection techniques were observation, interviews, and documentation. The study concluded that among the four indicators of sociomathematical norms, three indicators of male students are superior to female students. Male students are superior in accepting explanations from teachers, accepting differences of opinion, and mathematical insight. Meanwhile, female student excels in only one indicator (the effectiveness of mathematics).